Caravan Routes Linking Khorazm With Areas of Southwest Asia in the Early Modern Period - Nigora Allaeva (Researchparks Publishing, 2022)
The article covers the issue of caravan routes that connected Khorezm and the neighboring khanates, as well as the Russian state, with the regions of Southwest Asia, including Khorasan, Iran, and the Ottoman Empire, in the late Middle Ages. It shows the important geostrategic and transit importance of Khorezm by comparing important land and land waterway trade routes with various sources, including archaeological materials and written sources.